Belarusian Folk Dialects on the Atlas Maps - Jankowiak, Mirosław (Slavistica Vilnensis, 2025)
Białoruskie gwary ludowe na mapach atlasu: KURCOVA VERANIKA MIKALAJEUNA, 2024, Leksičny atlas belaruskich narodnych havorak. Analityčnyja i davedačna-infarmacyjnyja materyjaly, Minsk: Centr dasledavanniaŭ belaruskaj kul’tury, movy i litaratury NAN Belarusi, 572 ss. [В.М. Курцова, Лексічны атлас беларускіх народных гаворак. Аналітычныя і даведачна-інфармацыйныя матэрыялы, Мінск: Цэнтр даследаванняў беларускай культуры, мовы і літаратуры НАН Беларусі, С. 572], ISBN: 978-985-08-3191-0. This review discusses the extensive monograph “Leksičny atlas belaruskich narodnych havorak. Analityčnyja i davedačna-infarmacyjnyja materyjaly” [en. Lexical Atlas of Belarusian Folk Dialects. Analytical and Informational Materials]. In six chapters, the author collects, organizes, and systematizes available knowledge on one of the most important works in Belarusian dialectology and Belarusian linguistics – the five-volume Lexical Atlas of Belarusian Folk Dialects, published between 1993 and 1998. The reader will learn about the authors of the Atlas, the history of its creation, its structure, the types of maps, the origins of the idea for the Atlas, how its concept was developed, etc. The publication also includes valuable materials such as lists of maps, surveyed points, an alphabetical list of all lexemes shown on the maps, etc. The book under review is not only an important supplement to the Lexical Atlas of Belarusian Folk Dialects, but also a stand-alone scientific, analytical, and informative work, constituting a valuable source of information of a broader nature – notably, about Belarusian linguistic geography, the history of Belarusian dialectology, and dialectologists.